Late Cenozoic Bryozoa from diamictites of Cape Lamb, Vega Island, Antarctic Peninsula - Adamonis Susana; Hara Urszula; Concheyro Andrea (Polish Polar Research, 2015)
Bryozoans were found in upper Cenozoic diamictite debris that crops out at the southwestern tip of Cape Lamb, Vega Island. The diamictite is the youngest deposit on the island and richly composed of foraminifers, brachiopods and scallops. The foraminifera assemblage recovered from the Cape Lamb diamictite and 87Sr/86Sr isotopic age obtained from the pectinid Adamussium colbecki in the nearby locality of Terrapin indicates a Pleistocene age for this deposit. The main goal of this contribution is to present a bryozoan assemblage of Microporella stenoporta Hayward et Taylor, Hippothoa flagellum Manzoni, Ellisina antarctica (Kluge), Micropora notialis Hayward et Ryland and an indeterminate crisiid constituting the first record of these bryozoan taxa in Cenozoic diamictites of the Antarctic Peninsula.